New Azacycles by One‐Pot Three‐Component Hantzsch‐Like Synthesis of Tetra(hexa)azacyclopenta[a]anthracenes, Tetraazaindeno[5, 4‐b]fluorenes, and Oxatetraazacyclopenta[m]tetraphenes. Issue 3 (28th February 2023) - Abdelmoniem, Amr M.; Ramadan, Muhammed A.; Ghozlan, Said A. S.; Butenschön, Holger; Abdelhamid, Ismail A.
Abstract: New Azacycles by One‐Pot Three‐Component Hantzsch‐Like Synthesis of Tetra(hexa)azacyclopenta[ a ]anthracenes, Tetraazaindeno[5, 4‐ b ]fluorenes, and Oxatetraazacyclopenta[ m ]tetraphenes (H. Butenschön, I. A. Abdelhamid et al.) #OpenAccess Multicomponent reactions (MCRs) are envisaged as an entry point for the synthesis of heterocyclic compounds with interesting biological activities. An efficient approach to annelated tetra(hexa)azacyclopenta[ a ]anthracenes, tetraazaindeno[5, 4‐ b ]fluorenes, and oxatetraazacyclopenta[ m ]tetraphene was accomplished using a three‐component reaction involving 7‐amino‐2‐methyl‐3‐phenylpyrazolo[1, 5‐ a ]pyrimidin‐5‐one with aromatic aldehydes and the corresponding active 1, 3‐dicarbonyl compounds (namely, dimedone, 1, 3‐dimethylbarbituric acid, 1, 3‐indanedione, and 4‐hydroxycoumarine). The reactions were conducted in glacial acetic acid at reflux for 5 h to give the desired products in good yields (62–83 %). The chemical constitutions of all new products were confirmed spectroscopically. Abstract : An efficient approach to annelated tetra(hexa)azacyclopenta[ a ]anthracenes, tetraazaindeno[5, 4‐ b ]fluorenes, and oxatetraazacyclopenta[ m ]tetraphene was accomplished via the one pot three‐component reaction involving 7‐amino‐2‐methyl‐3‐phenylpyrazolo[1, 5‐ a ]pyrimidin‐5‐one with aromatic aldehydes and the corresponding active 1, 3‐dicarbonyl compounds (namely, dimedone, 1, 3‐dimethylbarbituric acid, 1, 3‐indanedione, and 4‐hydroxycoumarine)